Growth response, chlorophyll content, and nitrate reductase activity of mustard greens (Brassica rapa L.) to salinity stress post application of biofertilizer in hydroponic system - Hasna Fatin Affifah; Dwi Umi Siswanti (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.